1989
DOI: 10.1021/bi00437a027
|View full text |Cite
|
Sign up to set email alerts
|

Binding of thiocyanate to lactoperoxidase: proton and nitrogen-15 nuclear magnetic resonance studies

Abstract: The binding of thiocyanate to lactoperoxidase (LPO) has been investigated by 1H and 15N NMR spectroscopy. 1H NMR of LPO shows that the major broad heme methyl proton resonance at about 61 ppm is shifted upfield by addition of the thiocyanate, indicating binding of the thiocyanate to the enzyme. The pH dependence of line width of 15N resonance of SC15N- in the presence of the enzyme has revealed that the binding of the thiocyanate to the enzyme is facilitated by protonation of an ionizable group (with pKa of 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…Most interactions of mineral anions such as chloride, nitrate (Galanter & Labotka, 1991) or thiocyanate (Modi et al, 1989b;Crull & Goff, 1993) are of the same order of magnitude in a number of different proteins. Again, these studies support the observation that, even though thiocyanate is a particular polarizable soft agent, it does not differ from others anions: in the particular case of BPTI, we have observed that sodium chloride is also able to form pentamers of BPTI in crystals,…”
Section: The Thiocyanate Ions and Their Role In Decamer Buildingmentioning
confidence: 99%
“…Most interactions of mineral anions such as chloride, nitrate (Galanter & Labotka, 1991) or thiocyanate (Modi et al, 1989b;Crull & Goff, 1993) are of the same order of magnitude in a number of different proteins. Again, these studies support the observation that, even though thiocyanate is a particular polarizable soft agent, it does not differ from others anions: in the particular case of BPTI, we have observed that sodium chloride is also able to form pentamers of BPTI in crystals,…”
Section: The Thiocyanate Ions and Their Role In Decamer Buildingmentioning
confidence: 99%
“…Under fast exchange condition$, the measured relaxation rate, R, <,h\ ( = I / TI,obJ, is the weighted average of the relaxation rates of the free and bound substrate (Rl,f and R, ,,, respectively), (Sakurada et al, 1986;Modi et al, 1989). Under the experimental conditions (substrate concentration much greater than protein concentration), pf = 1, and if a stoichiometry of 1 : 1 is assumed, Eqn (5) is derived, (5) where E, and S, represent the total concentrations of APX-CN and substrate, respectively, and Kd is the dissociation constant of the protein I substrate complex (Sakurada et al, 1986;Modi et al, 1989). In the present experiments, determination of R,,,,, which represents the paramagnetic contribution to the relaxation rate of the protons in the bound substrate arising from the unpaired electrons of the haem iron, is required.…”
Section: Equilibrium Binding Measurementsmentioning
confidence: 99%
“…Because it is very difficult to study the binding to compound I that causes the reaction, the binding of these ions to peroxidases in the resting state was examined by spectrophotometric (4,7,8), kinetic (9,10), fluorometric (11), 127 I NMR (12,13), 15 N NMR (14 -17), 13 C NMR (17), 1 H NMR (13)(14)(15)(16)(17)(18)(19), and optical difference spectroscopy (20 -22) techniques. The actual site of the binding of these ions to the enzymes and the mechanism of electron transfer from these ions to the heme irons have yet to be clarified.…”
mentioning
confidence: 99%